Role of Autophagy in Preeclampsia - Nurrani M. Dewi; Rina Triana; Angliana Chouw; Siska Darmayanti (Universitas Padjadjaran, 2020)
Autophagy is essential in cell death decisions and can protect cells by preventing them from undergoing apoptosis. Autophagy contributes to a variety of physiological processes, including cell differentiation and various functions in embryogenesis. Some studies reported that the expressions of autophagy-related (Atg) proteins are found in placentas. This review article was focusing on the autophagy process and some Atg proteins which are involved in human placentation, especially in preeclampsia cases, since it has been well known that abnormal placentation and placenta dysfunction has crucial role in its development. Preeclampsia cannot be related to a single cause and the underlying mechanism of it is still not clearly understood. Recent hypothesis regarding the cause of preeclampsia is more focused on the inadequate trophoblast invasion and placentation. Scientists also suggested that other mechanism might be associated with this condition in preeclampsia, which is autophagy. Autophagy is a mechanism that essential for cellular remodeling which occurs during the development of multicellular organisms in the special process, by expressing an “eat-me” signal and cleared by neighboring cells. In preeclampsia patients, autophagy has an important role in trophoblast function under physiologically low oxygen conditions. The activation of autophagy in preeclampsia is shown by the different level of abundance of key protein of the Atg pathway. Some Atg proteins known to be related to preeclampsia are Beclin-1, LC3, and p62.Keywords: Atg proteins, cell death, embryogenesis, placentation Peran Autofagi dalam PreeklampsiaAbstrakAutofagi memiliki peran yang penting dalam keputusan kematian sel dan dapat melindungi sel dengan cara mencegahnya mengalami apoptosis. Autofagi berkontribusi pada berbagai proses fisiologis, termasuk diferensiasi sel dan berbagai fungsi dalam embriogenesis. Beberapa penelitian melaporkan bahwa ekspresi protein Atg ditemukan di plasenta. Artikel review ini berfokus pada proses autofagi dan beberapa protein autophagy-related (Atg) yang terlibat dalam plasentasi, terutama pada kasus preeklampsia, karena telah diketahui bahwa plasentasi abnormal dan disfungsi plasenta memiliki peran yang penting dalam perkembangan. Preeklampsia tidak dapat dikaitkan dengan satu penyebab saja, dan mekanisme yang mendasarinya masih belum dipahami secara jelas. Hipotesis terbaru mengenai penyebab terjadinya preeklampsia lebih terfokus pada invasi trofoblast yang tidak memadai dan kesalahan plasentasi. Para ilmuwan juga menyarankan bahwa mekanisme lain yang mungkin terkait dengan kondisi ini adalah autofagi. Autofagi adalah mekanisme yang penting untuk pemodelan ulang seluler yang terjadi selama perkembangan organisme multiseluler dalam proses khusus, dengan mengekspresikan sinyal “makan-saya” dan kemudian dibersihkan oleh sel tetangga. Pada pasien preeklampsia, autofagi memiliki peran penting dalam fungsi trofoblas di bawah kondisi oksigen rendah. Pengaktifan autofagi pada preeklampsia ditunjukkan oleh perbedaan tingkat kelimpahan protein utama dari pathway Atg. Beberapa protein Atg yang diketahui terkait dengan preeklampsia adalah Beclin-1, LC3, dan p62.Kata kunci: Embriogenesis, kematian sel, plasentasi, protein Atg